Membangun Keterampilan Komunikasi Peserta Didik Madrasah: Eksplorasi Pelibatan Kegiatan Muhadharah dalam Proses Pembelajaran - Aulia Sudrajat, Adisti; Hidayati, Noorazmah; Abdullah, Abdullah (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
This study aims to describe muhadarah activities can build students' communication skills at MTs Muslimat NU Palangka Raya. There have been problems with students' lack of ability to communicate, lack of self-confidence, fear and so on. Muhadarah activities are activities to deliver speeches or lectures related to religion or achieve goals, especially in communication skills. The method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The results of the study indicate that muhadarah activities are carried out routinely and in a structured manner, and have a positive impact on communication skills. This can be seen from the increase in good communication skills, self-confidence, assertiveness and self-control. The conclusion is that muhadarah activities can run effectively if they are carried out consistently and receive maximum guidance. Suggestions are given to continue to develop the implementation of muhadarah activities in line with Islamic values and can help students' communication skills, as reflected in the verses of the Qur'an, one of which is QS. An-Nahl verse 125 and the hadiths of the Prophet SAW.